(3SdWI GdbVGA ai JMQjc GdOYhi GdLfGFjI (B: s (3OQGSI ebGQfI (B/ s - (3NGdO Ydi eMeO GdeSGeQI GdYbjdGJ s; (3MSfjf EHQGgje UGdM YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JYGdL gPg GdQSGdI UdGMjI eMceI GdehVhY HGdJUOj ddOYGhi GdLRGFjI HJMQjcgG h GdaUd ajgG aj HYV GdCMjGf(B: (3h eOi JYGQV Ch GJSGb gPG GdOhQ ddeMGce GdLfGFjI eY OhQ GdfjGHI GdYGeI ai JMQjc GdOYhi GdLfGFjI(B: (3h eOi JCKQ SdWI GdbGVi GdLfGFi HeG jYQV CeGeg ef h bGFY echfg ddQcf GdeGOi ddLQGFe(B: (3aVdkG eOi JCKjQ gPG GdOhQ ddeMGce GdLfGFjI Ydi eHOC GdeMGceI GdYGOdI(B: (3h eHOC TNUjI GdOYhi GdLfGFjI(B: (3HGdGVGaI Gdi eOi JHfi GdeTQY ddVeGfGJ GdbGfhfjI GdJi JMbb GdeMGceI GdYGOdI(B: (3h eOi JMbjbg deHOC GdaUd Hjf SdWI GdGJgGe h SdWI GdMce(B: (3Ydi fMh dG jDKQ HGdeMGceI GdYOGdI(B: (3h dG jMhd Ohf GadGJ GdLfGI ef GdYbGH(B: (3MjK jNJda ehba GdJTQjYGJ GdebGQfI HGdfSHI dMb GdeMGce HGdJUOi h JMQjc GdOYhi GdLfGFjI h GdMce ajgG(B: (3EP JhLO bhGfjf JVjb ef fWGb gPG GdMb(B: (3ai Mjf Cf gfGc bhGfjf JJhSY ajg(B: (3h GdSHH ai Pdc deG jJeJY Hg gPG GdehVhY ef CgejI defGbTJg YdGbg gGeI Hjf SdWJi GdGJgGe h GdMce(B: (3h eG eOi Mb SdWI GdMce HeQGbHI SdWI GdGJgGe HeG Jbhe Hg ef CYeGd(B: (3h eJi jMb dgG JhLjI SdWI GdGJgGe dJMQjc GdOYhi GdLfGFjI Yf hbGFY h ETNGU LOO(B: (3ceG JfGbT Mb GdJUOj HGdfSHI dLQGFe GdLdSGJ h GdSdWI GdJi JJeJY HgG GdeMGce ef JMQjc GdOYhi GdLfGFjI Yf Jdc GdLQGFe h GdaUd ajgG(B: (3h cPdc ffGbT Mb eMceI GdGSJFfGa HGdJUOj dehVhY GdOYhi ai MGdI HWdGf Mce eMceI Chd OQLI ShGA ddHWdGf ai GdEMQGAGJ Ch ai GdMce PGJgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2016s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B344-355s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdOYhi GdLfGFjIs; (3JMQjc GdOYhi GdLfGFjIs; (3SdWI GdeMGces; (3eMceI GdLfGjGJ s; (3eMceI GdGSJFfGa s; (3LQGFe GdLdSGJ s; (3GdfbVs; (3GdOYhi GdLfGFjI s; (3LQGFe GdbGfhf GdYGe aj GdLdSI s; (3GdLQGFe GdJj JNd HGdGMJQGe GdhGLH ddeMceI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs